A micro-channel liquid cooling based carbon fiber honeycomb sandwich cabin panel and manufacturing method
By employing a microchannel liquid-cooled carbon fiber honeycomb sandwich structure in aerospace vehicle cabins, the problems of the contradiction between lightweight and high thermal conductivity, the accumulation of interfacial thermal resistance, the mismatch of thermal expansion, and insufficient passive heat storage have been solved, achieving efficient thermal management and integrated structural design.
Patent Information
- Application Number
- CN202610701097.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-20
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-05-20
AI Technical Summary
Existing aerospace cabin structures struggle to balance lightweight design with high thermal conductivity. Functional separation design leads to accumulated interfacial thermal resistance and system redundancy. The anisotropic thermal conductivity of carbon fiber composites limits heat transfer. In extreme environments, thermal expansion mismatch and passive heat storage cannot cope with continuous high heat flux.
The carbon fiber honeycomb sandwich structure based on microchannel liquid cooling is adopted. By embedding microchannels in the honeycomb core layer, combined with high thermal conductivity carbon fiber panels and thermally enhanced interfaces, the load-bearing and heat dissipation are integrated. The honeycomb cavities are filled with phase change materials to buffer the thermal load.
It achieves a synergy between high in-plane thermal conductivity and low areal density, eliminates interfacial thermal resistance, improves temperature uniformity, adapts to extreme environments, and possesses modular maintainability and efficient thermal management capabilities.
Smart Images

Figure CN122540405B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermal control technology for aerospace structures, specifically to a carbon fiber honeycomb sandwich panel based on microchannel liquid cooling and its manufacturing method, which is particularly suitable for spacecraft compartments with densely arranged high-power-density electronic equipment. Background Technology
[0002] In aerospace vehicle cabin structural design, lightweighting and thermal management are two core and mutually restrictive technical requirements. With the continuous increase in the power density of onboard computing devices (single-chip heat flux density has already exceeded...), the situation is further complicated by the fact that... The traditional structural-functional separation design model faces severe challenges. Analysis reveals the following main technical deficiencies in existing technologies:
[0003] I. The fundamental contradiction between lightweight design and high thermal conductivity Carbon fiber composite honeycomb sandwich structures exhibit excellent specific stiffness (bending stiffness / area density can reach more than 10 times that of steel), and the area density can be controlled to be less than [value missing]. However, the thermal conductivity in the thickness direction is extremely low (less than 1 W / m·K), making it unable to effectively conduct and dissipate the heat generated by high-power electronic devices. Specifically, the thermal conductivity along the fiber direction of high-modulus pitch-based carbon fibers (such as K13D2U) can reach 800 W / m·K, but due to the limitations of the resin matrix (volume fraction of about 50%) and interlayer interfaces, the out-of-plane thermal conductivity of CFRP laminates is only 0.5-1.0 W / m·K; the thermal conductivity in the thickness direction of carbon fiber honeycomb sandwich structures is even lower, at 0.2-0.22 W / (m·K), mainly limited by the high porosity (82-91%) of the honeycomb core and the thermal resistance of the adhesive.
[0004] On the other hand, although high thermal conductivity metals (copper, aluminum) have high thermal conductivity (167-398 W / m·K), they also have high density. If used as a substrate to manufacture liquid cooling plates, the areal density often exceeds [a certain value]. This poses a serious conflict with the stringent areal density constraints of aerospace vehicles. Existing technologies have failed to achieve a synergistic balance between "structural lightweighting" and "efficient heat dissipation" within the same structural body.
[0005] II. Functional separation leads to system redundancy and accumulation of interface thermal resistance. Traditional solutions employ a separate design of "carbon fiber honeycomb load-bearing structure + independent metal liquid cooling plate." The liquid cooling plate needs to be installed on the surface of the load-bearing structure using fasteners, with a thermally conductive interface material filling the space between the two. According to thermal resistance network analysis, each additional interface introduces contact thermal resistance. This can increase the overall thermal resistance by 20-30%. Furthermore, the separate design increases system complexity, overall weight, and assembly time. For example, the lightweight spacecraft main structure disclosed in patent CN107745829B only focuses on structural load-bearing functions and does not involve integrated thermal management design; while the structurally integrated wing antenna disclosed in patent CN103887605A integrates liquid cooling channels, it is machined internally from sheet metal, resulting in a relatively large weight.
[0006] III. Limitations of Anisotropic Thermal Conductivity in Carbon Fiber Composites The difference between the in-plane and out-of-plane thermal conductivity of CFRP is enormous (reaching over 100:1). Although the thermal conductivity in the thickness direction can be improved to 0.6-16.8 W / m·K through carbon nanotube interface enhancement technology, it is still difficult to meet the requirements of efficient heat dissipation. In high power density applications, heat conduction along the thickness direction is difficult, which can easily lead to the formation of local hot spots below the mounting area of electronic devices, causing the chip junction temperature to exceed the limit and affecting the reliability and lifespan of electronic devices.
[0007] IV. Insufficient adaptability to extreme environments Existing metal-based liquid cooling plates mostly use copper and aluminum materials, which have the following problems: (1) There is a risk of gas release (water vapor, organic matter volatilization) in the vacuum environment of space, which may contaminate the optical payload; (2) The coefficient of thermal expansion of metals is relatively low. carbon fiber main structure of spacecraft The severe mismatch leads to thermal stress under orbital thermal cycling (-150℃ to +125℃), resulting in loose connections, seal failure, and even structural fatigue cracking. The microchannel cooling technologies disclosed in patents US5801442A and US6942018B2 both use metal or silicon as substrates and do not consider adaptability to the extreme aerospace environment.
[0008] V. Passive thermal storage cannot cope with continuous high heat flow. Some existing technologies employ phase change materials for passive heat storage (such as patent CN114154243A), which can absorb transient heat loads in a short period. However, when faced with continuous high-power heat dissipation demands (such as long-term on-orbit computing tasks), the heat storage capacity of phase change materials is limited (latent heat per unit mass is approximately 150-250 kJ / kg). The heat must ultimately be dissipated through radiation or convection; otherwise, it will gradually heat up and fail. Simply relying on passive heat storage cannot solve the problem of continuous high heat flux.
[0009] Therefore, there is an urgent need in this field for a method that can meet the stringent areal density limits of aerospace vehicles. Under the premise of achieving a load-bearing and heat dissipation integrated cabin structure with high in-plane thermal conductivity (greater than 50W / m·K) and efficient active heat dissipation (heat flux density greater than 500W / cm²), the structure should have a thermal expansion coefficient that matches the main structure of the spacecraft, adaptability to the vacuum environment of space, and modular maintainability. Summary of the Invention
[0010] In view of the above analysis, the present invention aims to provide a carbon fiber honeycomb sandwich panel based on microchannel liquid cooling and its manufacturing method, in order to solve one of the technical problems in the prior art, such as the contradiction between lightweight and high thermal conductivity, which makes it difficult to balance the areal density and heat dissipation capacity; the accumulation of interfacial thermal resistance and system redundancy caused by functional separation; local hot spots caused by anisotropic thermal conduction limitations; thermal expansion mismatch and gas release problems under extreme environments; and the inability of passive thermal storage to cope with continuous high heat flux.
[0011] The objective of this invention is mainly achieved through the following technical solutions: This invention provides a carbon fiber honeycomb sandwich panel based on microchannel liquid cooling, comprising: The upper panel (1) and the lower panel (2) are made of high thermal conductivity carbon fiber prepreg by hot pressing and curing, and are set as the skin of the honeycomb sandwich structure to bear the in-plane load and in-plane heat conduction; The honeycomb core layer (3) is fixed between the upper panel (1) and the lower panel (2), and adopts a carbon fiber paper honeycomb core or an aramid paper honeycomb core. The honeycomb cavities (31) of the honeycomb core layer (3) serve as components of the coolant flow channel. The honeycomb core layer (3) is composed of a regular hexagonal honeycomb structure made of carbon fiber paper. The microchannel liquid cooling system is embedded in the honeycomb grid cavity (31) inside the honeycomb core layer (3), including microchannel pipes (4) passing through the honeycomb grid cavity (31). The thermally enhanced interface (7) is used to reduce the out-of-plane thermal resistance between the upper panel (1), the lower panel (2) and the honeycomb core layer (3), to diffuse the heat of the panel along the in-plane direction to the area covered by the microchannel pipeline (4), and to eliminate the gap thermal resistance between the microchannel pipeline (4) and the surrounding structure.
[0012] Furthermore, the thermally enhanced interface (7) includes: a first adhesive layer (71) coated between the upper panel (1), the lower panel (2) and the honeycomb core layer (3), a pyrolytic graphite foil (72) embedded in the top and bottom of the honeycomb cell (31), and a second adhesive layer (73) filled between the pyrolytic graphite foil (72) and the microchannel pipeline (4).
[0013] Furthermore, the first adhesive layer (71) is a modified epoxy resin adhesive doped with 1-5 wt% graphene nanosheets, with a layer thickness of 0.1-0.3 mm and a thermal conductivity of 1.5-3.0 W / m·K; the second adhesive layer (73) is a high thermal conductivity silicone grease or an organosilicon adhesive doped with ceramic fillers, with a thermal conductivity of 2-5 W / m·K.
[0014] Furthermore, the pyrolytic graphite foil (72) has a thickness of 0.03-0.15 mm and an in-plane thermal conductivity of 1000-1800 W / m·K, and is disposed on the entire surface area or local high thermal conductivity area at the top and bottom of the honeycomb cell cavity (31).
[0015] Furthermore, the microchannel liquid cooling system also includes a manifold (5) disposed at the edge of the cabin plate and connected to the end of the microchannel pipeline (4), and an interface (6) disposed on the side of the cabin plate and connected to the manifold (5).
[0016] Furthermore, the upper panel (1) and the lower panel (2) are made of high-modulus pitch-based carbon fiber prepreg with a fiber volume fraction of 50-60%, a panel thickness of 0.3-0.8 mm, an in-plane thermal conductivity greater than 300 W / m·K, and a layup pattern of [0° / 90° / 0° / 90°] symmetrical layup or quasi-isotropic layup.
[0017] Furthermore, the microchannels (4) are arranged in an "S" shape in a continuous manner, a "Z" shape in a gradual manner, a concentric circle arrangement, or a radial arrangement within the honeycomb core layer (3).
[0018] Furthermore, the honeycomb core layer (3) has a guide hole (32) pre-processed in the area through which the microchannel pipeline (4) passes. The diameter of the guide hole (32) is 0.1-0.3 mm larger than the outer diameter of the microchannel pipeline (4).
[0019] Furthermore, it also includes a phase change material heat storage layer (8), which fills the area inside the honeycomb cavity (31) where no microchannel pipeline (4) is arranged. The phase change material heat storage layer (8) is made of composite phase change material with a phase change temperature of 40-70℃ and a latent heat of 150-250kJ / kg.
[0020] Furthermore, the microchannel liquid cooling system adopts a double-layer arrangement. A horizontal partition is set in the middle of the thickness direction of the honeycomb core layer (3) to divide the core layer into upper and lower sub-cavities. Microchannel pipelines (4) are arranged in each sub-cavity, and the two layers of pipelines are connected by a vertical connecting pipe.
[0021] Furthermore, the outer surfaces of the upper panel (1) and the lower panel (2) are provided with functional coatings, including at least one of an electromagnetic shielding coating, an antigenic oxygen coating, and a high emissivity thermal control coating.
[0022] Furthermore, the honeycomb core layer (3) has a regular hexagonal honeycomb structure with a side length of 3-10 mm, a core layer height of 5-20 mm, a honeycomb wall thickness of 0.05-0.1 mm, and a density of [missing information]. .
[0023] Furthermore, the microchannel pipeline (4) is made of metal thin tube with an outer diameter of 0.5-2.0 mm and a wall thickness of 0.05-0.2 mm. The outer surface of the pipeline is roughened and the surface roughness Ra≥3.2 μm. The pipeline has a pressure resistance design pressure ≥1.5MPa and a burst pressure ≥3.0 MPa.
[0024] Furthermore, the ratio of the total length of the flow channel of the microchannel (4) to the area of the cabin plate is: The coolant flow rate is controlled at 0.1-0.5 m / s, and the pressure drop is <1 MPa.
[0025] The present invention also provides a spacecraft cabin structure, including the aforementioned carbon fiber honeycomb sandwich panel based on microchannel liquid cooling.
[0026] This invention also provides a method for manufacturing a carbon fiber honeycomb sandwich panel based on microchannel liquid cooling, comprising the following steps: S1: High thermal conductivity carbon fiber prepreg is used to lay up the layers according to the designed layup angle and sequence, and then hot-pressed and cured for 30-120 minutes at a temperature of 120-180℃ and a pressure of 0.5-1.5MPa to prepare the upper panel (1) and the lower panel (2). S2: Cut the carbon fiber paper honeycomb core or aramid paper honeycomb core according to the size of the cabin plate, process guide holes (32) at the predetermined insertion positions, and insert titanium alloy or stainless steel thin tubes with surface micro-arc oxidation treatment into the honeycomb cell cavity (31) through the guide holes (32) to form microchannel pipelines (4). The end of the microchannel pipeline (4) is connected to the manifold (5), and the air tightness is tested after connection. S3: Set up a thermally enhanced interface (7): Apply an epoxy resin adhesive containing graphene nanosheets to the bonding surface of the top plate (1), the bottom plate (2) and the honeycomb core layer (3) to form a first adhesive layer (71), lay pyrolytic graphite foil (72) on the top and bottom of the honeycomb cavity (31), and form a second adhesive layer (73) between the pyrolytic graphite foil (72) and the microchannel pipeline (4) with high thermal conductivity silicone grease or silicone adhesive. S4: Assemble the upper panel (1), lower panel (2), honeycomb core layer (3), microchannel pipeline (4) and thermally enhanced interface (7) in sequence in the assembly fixture, apply a uniform pressure of 0.1-0.3MPa, and cure at a temperature of 80-120℃ for 2-6 hours to form a load-bearing and heat dissipation integrated compartment.
[0027] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: (1) Synergistic achievement of lightweight and high thermal conductivity By employing the technical feature of "embedding microchannels inside the honeycomb core layer," and utilizing the honeycomb cavities as components of the coolant flow channels, the heavy metal substrate (typically 3-10mm thick) of traditional liquid cooling plates is fundamentally eliminated, thereby allowing the surface density of the cooling plate to be controlled within a certain range. It meets the stringent requirement of less than 5 kg / m². Simultaneously, due to the adoption of a composite structure of "high thermal conductivity carbon fiber panel (in-plane thermal conductivity greater than 300 W / m·K) + pyrolytic graphite foil interface reinforcement (in-plane thermal conductivity 1000-1800 W / m·K)," an in-plane thermal conductivity greater than 50 W / m·K is achieved; and thanks to the use of an "embedded microchannel liquid cooling system," forced convection of coolant is achieved. This achieves an equivalent thermal conductivity in the thickness direction greater than 200 W / m·K, which is two orders of magnitude higher than that of traditional CFRP honeycomb structures (less than 1 W / m·K in the thickness direction).
[0028] (2) Integrated load-bearing and heat dissipation design eliminates interfacial thermal resistance Because of the integrated design that "embeds the microchannel liquid cooling system into the honeycomb sandwich structure and directly thermally couples it with the panel through the thermally enhanced interface", the thermal resistance of the thermal interface material in the traditional "load-bearing structure + independent heat dissipation device" separate design is eliminated, reducing the total thermal resistance by 20-30%; at the same time, because no additional fasteners and independent liquid cooling plates are required, the total mass of the system is reduced by 30-40%.
[0029] (3) Temperature uniformity is significantly improved, avoiding local hot spots. Thanks to the technical feature of "embedding pyrolytic graphite foil sheets into the top and bottom of the honeycomb lattice cavity", the heat from the local heat source is rapidly diffused to a larger microchannel coverage area by utilizing its high in-plane thermal conductivity (1000-1800W / m·K). Combined with "S-shaped, Z-shaped or other optimized microchannel pipelines", the coolant and the hot surface can form a sufficient heat exchange, and the temperature difference on the panel surface is controlled to be less than 5℃, which is significantly better than the 15℃ temperature difference of traditional aluminum-based liquid cooling plates.
[0030] (4) Strong adaptability to extreme environments Because it adopts a full composite material main structure of "carbon fiber panel + non-metallic honeycomb core", the overall coefficient of thermal expansion can be designed to match the carbon fiber main structure of the spacecraft. It avoids thermal stress fatigue caused by CTE mismatch under orbital thermal cycling environment; because the main material is a composite material, the vacuum outgassing rate is less than It meets the requirements of NASASP-R-0022A standard; because the microchannel uses titanium alloy, stainless steel or corrosion-resistant alloy tubes instead of a whole metal plate, the amount of metal used and the structural weight are greatly reduced, while ensuring pressure resistance (design pressure greater than 1.5MPa) and long-term service reliability.
[0031] (5) Scalability and on-orbit maintainability Thanks to its modular design, the density and path of the microchannels can be adjusted according to the heat load distribution. Different power consumption scenarios can be adapted by changing the number, diameter, cross-sectional shape and arrangement of the tubes. Thanks to its edge manifold design, it is easy to form a standardized interface with the external pump-driven cooling circuit. Thanks to the open cavity structure of the honeycomb core layer, damaged microchannel tubes can be replaced or repaired on orbit by locally cutting the adhesive layer, pulling out the old tube and inserting the new tube.
[0032] (6) Transient heat load buffering capacity Due to the adoption of the technical feature of "filling the area of the honeycomb cell without microchannels with a phase change material heat storage layer", it can absorb excess heat during short-term peak power consumption of electronic devices (such as the moment of power-on or large data processing), maintain the phase change temperature in the range of 40-70℃, smooth heat flow fluctuations, reduce the instantaneous demand on coolant flow, and improve the robustness of the entire thermal control system. Attached Figure Description
[0033] Figure 1 This is a schematic diagram of the overall structure of a carbon fiber honeycomb sandwich panel based on microchannel liquid cooling. Figure 2 This is a schematic diagram showing the arrangement of the honeycomb core layer and the microchannel tubing in the thickness direction; Figure 3 A detailed schematic diagram of the layered structure of the thermally enhanced interface; Figure 4 This is a schematic diagram of the microchannels arranged in an "S" shape within the honeycomb core layer. Figure 5 This is a process flow diagram of the manufacturing method.
[0034] Reference numerals: 1-Top panel; 2-Lower panel; 3-Honeycomb core layer; 31-Honeycomb cell; 32-Guide hole; 4-Microchannel pipeline; 5-Channel; 6-Interface; 7-Temperature-enhanced interface; 71-First adhesive layer; 72-Pyrolytic graphite foil; 73-Second adhesive layer; 8-Phase change material heat storage layer. Detailed Implementation
[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. It should be understood that these embodiments are only for explaining the invention and not for limiting the scope of protection of the invention.
[0036] Example 1 (Basic Implementation) like Figures 1-4As shown, this embodiment provides a carbon fiber honeycomb sandwich panel based on microchannel liquid cooling, with preferred external dimensions of 1000mm×500mm×15mm, designed for use in low-Earth orbit satellite platform modules.
[0037] like Figure 1 The compartment panel shown in this embodiment mainly includes: an upper panel 1, a lower panel 2, a honeycomb core layer 3, a microchannel liquid cooling system, a thermally enhanced interface 7, and a phase change material heat storage layer 8. The microchannel liquid cooling system further includes microchannel pipes 4, manifolds 5, and interfaces 6; the thermally enhanced interface 7 further includes a first adhesive layer 71, a pyrolytic graphite foil 72, and a second adhesive layer 73. The components and their assembly relationships are described in detail below with reference to the accompanying drawings.
[0038] I. Top panel 1 and bottom panel 2 In this embodiment, the upper panel 1 and the lower panel 2 are made of high-modulus pitch-based carbon fiber K13D2U prepreg. It should be noted that the type of carbon fiber used here is only an example. In practical applications, K1100, M55J, M60J or other high thermal conductivity pitch-based fibers can also be used, as well as mesophase pitch-based carbon fibers or polyacrylonitrile-based high-modulus carbon fibers treated with specific processes.
[0039] The fiber volume fraction can be selected within the range of 50-60%, and 55% is used in this example. The reason for selecting 50-60% is that if the volume fraction is too low, the fiber contact will be insufficient and the thermal conductivity will decrease; if it is too high, the resin content will be insufficient and the interlaminar shear strength will decrease. 55% is the balance point that takes into account both thermal conductivity and mechanical properties.
[0040] The layup can be a symmetrical layup of [0° / 90° / 0° / 90°], a cross layup of [0° / 90°], a quasi-isotropic layup of [0° / ±45° / 90°], or other layup schemes that meet mechanical and thermal conductivity requirements. This embodiment uses a symmetrical layup. A symmetrical layup can avoid warping deformation after curing, while ensuring uniform thermal conductivity in two orthogonal directions within the plane.
[0041] The thickness of a single prepreg layer is 0.125 mm, and the total thickness is 0.5 mm. Preferably, the panel thickness can be adjusted within the range of 0.3-0.8 mm. This range is chosen because: a thickness less than 0.3 mm results in insufficient structural stiffness, making it prone to buckling deformation under vibration of the launching section; a thickness greater than 0.8 mm increases the areal density, making it difficult to meet the requirement of less than 0.3 mm. Constraints.
[0042] After hot-press curing (temperature 150℃, pressure 1.0MPa, time 60min), the in-plane thermal conductivity of the upper panel 1 and the lower panel 2 is approximately 320W / m·K (greater than 300W / m·K), and the areal density is approximately 0.8kg / m² for each. This design utilizes the excellent in-plane thermal conductivity of high thermally conductive carbon fiber to rapidly diffuse the heat generated by electronic devices along the in-plane direction, avoiding heat accumulation in local areas. Furthermore, the extremely thin panel thickness and low areal density lay the foundation for controlling the overall cabin panel areal density to below 5kg / m², thus resolving the contradiction between lightweight design and high thermal conductivity.
[0043] The outer surface of the top panel 1 is coated sequentially with: 1. Electromagnetic shielding coating: Copper-nickel conductive paint, with a surface resistivity of less than 0.1 Ω / sq and a thickness of 25 μm; silver paste coating can also be used as an alternative. The reasons for choosing copper-nickel conductive paint are: low surface resistivity, good adhesion to carbon fiber, and good stability in the spatial environment.
[0044] 2. Anti-proton oxygen coating: A sputtered layer, 1.0 μm thick; alternatively, another method can be used. The sputtered layer thickness can be selected within the range of 0.5-2.0 μm. The reasons are: dense structure, strong ability to resist atomic oxygen erosion, and good matching with the thermal expansion coefficient of carbon fiber.
[0045] 3. High emissivity thermal control coating: Polyurethane black paint, emissivity 0.88; as an alternative, anodized coating or white paint, with emissivity greater than 0.85, can also be used. Reasons for choosing polyurethane black paint: high emissivity, low vacuum outgassing rate, and simple construction.
[0046] It should be noted that the coating type and thickness can be adjusted according to the specific orbital environment and usage requirements: low orbits can focus on antigenic oxygen coating, while medium and high orbits can reduce or omit antigenic oxygen coating; in scenarios with high electromagnetic shielding requirements, the coating thickness can be increased or multi-layer shielding can be used. The outer surface of the lower plate 2 can be coated with an appropriate thermal control coating as needed, usually a high emissivity coating to enhance heat dissipation through radiation into deep space.
[0047] II. Honeycomb Core Layer 3 In this embodiment, the honeycomb core layer 3 is made of carbon fiber paper honeycomb core. As an alternative, aramid paper honeycomb core (such as Nomex honeycomb), glass fiber paper honeycomb core, or other lightweight high-strength honeycomb materials can also be used—the selection is mainly based on mechanical performance requirements, thermal conductivity requirements, and cost considerations.
[0048] The honeycomb core layer 3 has a regular hexagonal honeycomb structure, and the side length of the honeycomb can be selected within the range of 3-10mm. In this embodiment, 5mm is selected. The reason for selecting 3-10mm is that if the side length is less than 3mm, the honeycomb density will be too high and the weight will increase; if the side length is greater than 10mm, the critical buckling load of the honeycomb wall will decrease, affecting the compressive strength. 5mm is a commonly used value.
[0049] The core layer height can be selected within the range of 5-20mm; in this embodiment, 14mm is chosen. The core layer height affects the overall bending stiffness of the compartment and the flow channel space: if the height is less than 5mm, the bending stiffness is insufficient and microchannel pipelines cannot be arranged; if it is greater than 20mm, the surface density increases and it is not conducive to interface adaptation with external equipment.
[0050] The cell wall thickness can be selected within the range of 0.05-0.1mm; in this embodiment, 0.08mm is used. The selection of wall thickness needs to balance strength and weight: if the wall thickness is less than 0.05mm, the compressive strength of the cell will be too low; if it is greater than 0.1mm, the cell density will increase significantly.
[0051] Density can be The selection is within the range; this embodiment takes approximately... Density is lower than Then the mechanical properties are insufficient; higher than This reduces the weight advantage.
[0052] The honeycomb cell 31 is a hexagonal prism space with a side length of 5mm and a height of 14mm, serving as the mounting cavity for the microchannel tubing. Guide holes 32 are pre-machined at the predetermined insertion positions of the microchannel tubing using CNC drilling. The diameter of the guide holes is 0.1-0.3mm larger than the outer diameter of the microchannel tubing; in this embodiment, it is 0.2mm larger (guide hole diameter 1.0mm), and the hole spacing is 20mm. The reason for the guide hole diameter being 0.1-0.3mm larger than the outer diameter of the tubing is that if the gap is too small, inserting the tubing will be difficult and the tubing surface will be easily scratched; if the gap is too large, the adhesive filler layer will be too thick, increasing thermal resistance.
[0053] In traditional honeycomb sandwich structures, the honeycomb core serves only as structural filler, and its high porosity (82-91%) actually hinders thermal conductivity. This embodiment innovatively incorporates the honeycomb cavities as part of the coolant flow channels, allowing the honeycomb core layer to maintain its excellent specific stiffness (providing out-of-plane load-bearing capacity) while also becoming a carrier for the active heat dissipation system. The guide holes solve the problem of difficult thin tube insertion, ensuring that the pipes can accurately travel along the predetermined path.
[0054] III. Microchannel Liquid Cooling System The microchannel liquid cooling system includes a microchannel pipe 4, a manifold 5, and an interface 6.
[0055] Microchannel tubing 4: In this embodiment, microchannel tubing 4 uses a titanium alloy TA2 thin tube. The reason for choosing titanium alloy is its high specific strength, corrosion resistance, and thermal expansion coefficient, which is relatively close to that of carbon fiber. Furthermore, the vacuum outgassing rate is extremely low. As alternatives, stainless steel 316L (lower cost but slightly higher density and larger coefficient of thermal expansion), Inconel 625 or 718 (better temperature resistance, suitable for high-temperature environments near solar orbit), Ti-6Al-4V (higher strength titanium alloy), Hastelloy (excellent corrosion resistance), etc., can also be used. The pipe cross-sectional shape can also be selected according to actual needs: this embodiment uses a circular cross-section, but a flat rectangular cross-section (increasing the thermal contact area), an elliptical cross-section, a D-shaped cross-section, etc., are also perfectly feasible.
[0056] The outer diameter of the microchannel tube 4 can be selected within the range of 0.5-2.0 mm; in this embodiment, 0.8 mm is chosen. The reason for selecting an outer diameter of 0.5-2.0 mm is that if the outer diameter is less than 0.5 mm, processing will be difficult and the flow resistance will be too high; if it is greater than 2.0 mm, it will occupy too much space in the honeycomb cavity and affect the amount of phase change material filled. 0.8 mm is a comprehensive balance value.
[0057] The wall thickness of the microchannel conduit 4 can be selected within the range of 0.05-0.2mm; in this embodiment, 0.08mm is chosen. The selection of wall thickness must take into account both pressure resistance and weight: a wall thickness less than 0.05mm will result in insufficient pressure resistance (less than 1MPa); a wall thickness greater than 0.2mm will increase weight and increase the thermal resistance of the conduit wall.
[0058] The inner diameter of the microchannel conduit 4 is 0.4-0.8 mm, and in this embodiment, it is 0.64 mm. The outer surface of the conduit is treated with micro-arc oxidation (anodizing, chemical etching, sandblasting, laser roughening, etc. can also be used for surface roughening) to form a porous TiO2 ceramic layer with a thickness of 5-10 μm and a surface roughness Ra of approximately 4.0 μm (greater than or equal to 3.2 μm). The purpose of the surface roughening treatment is to increase the mechanical bonding strength with the adhesive and to increase the effective thermal contact area.
[0059] The microchannel pipeline 4 has a design pressure of ≥1.5MPa and a burst pressure of ≥3.0MPa. In this embodiment, the design working pressure is 1.0MPa and the burst pressure is ≥3.0MPa. The design pressure of 1.5MPa is based on the fact that the typical working pressure of a spacecraft cooling circuit is 0.5-1.0MPa, and a safety factor of 1.5 is used.
[0060] The arrangement of the microchannel tubing 4: In this embodiment, it is arranged in a continuous, meandering "S" shape within the honeycomb core layer 3 (e.g., Figure 4As shown in the diagram, 20 pipes are arranged running back and forth parallel to the long side of the cabin plate. The center-to-center distance between adjacent pipes can be selected within the range of 10-30mm; in this embodiment, 20mm is used. The reason for choosing a center-to-center distance of 10-30mm is that if it is less than 10mm, the pipes will be too dense, increasing flow resistance and weight; if it is greater than 30mm, the heat diffusion distance will be too large, increasing the risk of local hot spots. In addition to the S-shape, a "Z"-shaped gradual arrangement (in conjunction with a variable diameter manifold to achieve on-demand flow distribution), a concentric circular arrangement, and a radial arrangement can also be used. The reason for choosing the S-shape is that it is suitable for uniform heat source distribution, relatively simple to process, and provides uniform flow channel coverage.
[0061] The total flow channel length of microchannel 4 is approximately 15m, covering an area of... The ratio of the total length of the flow channel to the area of the cabin plate is Select from the range, in this embodiment it is .choose Reason: The ratio is less than The heat exchange area is insufficient; if it is greater than that, the heat exchange area is insufficient. This results in excessive flow resistance and increased pump power consumption.
[0062] The coolant flow rate is controlled within the range of 0.1-0.5 m / s; in this embodiment, 0.3 m / s is selected. The flow rate selection is based on the following: a flow rate below 0.1 m / s results in an excessively low convective heat transfer coefficient. If the pressure drop is higher than 0.5 m / s, the pressure drop will increase sharply (>1 MPa) and may cause pipeline vibration.
[0063] The cooling pressure drop in the microchannel pipeline 4 is less than 1 MPa. The reasons for choosing this pressure drop limit are: (1) Matching with the spacecraft pump-driven cooling system - the typical pump output pressure is 1.5-2.0 MPa, and the total system pressure drop needs to be controlled within 1.0 MPa to ensure normal circulation; (2) Structural sealing reliability - the risk of leakage at the connection between the microchannel pipeline 4 and the manifold 5 increases significantly when the pressure drop exceeds 1 MPa; (3) Stability of the phase change material heat storage layer - a higher pressure difference may cause leakage of the phase change material; (4) Weight and flow resistance balance - the heat exchange capacity and pump power consumption can be optimized under this limit; (5) Safety margin - 1 MPa is lower than the pipeline burst pressure (3.0 MPa) and the sealing interface pressure resistance (2 MPa), leaving sufficient safety margin.
[0064] Manifold 5 and Interface 6: Manifold 5 is located on the two short sides (500mm sides) of the cabin panel, made of 6061-T6 aluminum alloy (with a titanium-aluminum transition joint at the connection with the titanium alloy pipe), with an internal flow channel diameter of 5mm and a wall thickness of 1.0mm. It is used to evenly distribute the coolant to each microchannel pipe 4 and collect the return flow. In the Z-shaped arrangement, the manifold can adopt a variable diameter design (larger diameter at the inlet end and smaller diameter at the outlet end) to match the flow distribution. Interface 6 adopts an aerospace standard quick-disconnect connector (such as NASA standard or equivalent standard), with a pressure resistance of 2MPa and an O-ring seal, forming a detachable connection with the external pump-driven cooling circuit 11. The reason for choosing a quick-disconnect connector is to facilitate on-orbit maintenance and ground testing, and to ensure reliable sealing.
[0065] By integrating the manifold 5 into the edge of the compartment and setting the interface 6 on the side of the compartment, the liquid cooling system and the compartment body are structurally integrated. The modular interface design allows the compartment to be quickly connected / disconnected from the external cooling circuit, facilitating on-orbit maintenance and ground testing, thereby eliminating redundancy and assembly complexity caused by functional separation.
[0066] IV. Thermally Enhanced Interface 7 The thermally enhanced interface 7 is disposed between the upper panel 1, the lower panel 2 and the honeycomb core layer 3, and between the honeycomb core layer 3 and the microchannel pipeline 4. For example... Figure 3 As shown, in this embodiment, the thermally enhanced interface 7 includes a three-layer structure: a first adhesive layer 71, a pyrolytic graphite foil 72, and a second adhesive layer 73.
[0067] First adhesive layer 71: Coated between the upper panel 1, lower panel 2, and honeycomb core layer 3, using a modified epoxy resin adhesive (such as a modified version of 3MScotch-WeldDP420) doped with 1-5 wt% graphene nanosheets (GnP). The GnP sheet diameter can be selected in the range of 5-20 μm, and the thickness can be selected in the range of 1-10 nm. The reason for choosing a content of 1-5 wt% is that, as shown in Example 5, the thermal conductivity improvement is limited when the content is below 1% (only 1.2 W / m·K); when the content is above 5%, the shear strength drops below 10 MPa, which does not meet the structural requirements; 2-3 wt% is the preferred range that balances thermal conductivity and strength. In this example, 2 wt% is used, with a sheet diameter of 5-10 μm and a thickness of 5-10 nm. The adhesive layer thickness can be selected in the range of 0.1-0.3 mm, and in this example, 0.2 mm is used. Adhesive layer thickness selection: A thickness less than 0.1 mm cannot adequately fill the microscopic unevenness between the panel and the honeycomb core, resulting in air gaps; a thickness greater than 0.3 mm increases out-of-plane thermal resistance and the risk of adhesive layer cohesion failure. Thermal conductivity is increased from 0.2 W / m·K for pure resin to 1.5-3.0 W / m·K; in this embodiment, the measured value is 2.5 W / m·K. Alternatively, adhesives containing other high thermal conductivity fillers such as carbon nanotubes, diamond powder, boron nitride, and alumina can also be used.
[0068] Pyrolytic graphite foil 72: Embedded in the top and bottom of the honeycomb cell 31 (i.e., adjacent to the upper panel 1 and lower panel 2), using pyrolytic graphite foil with a thickness selectable in the range of 0.03-0.15mm; in this embodiment, 0.08mm is used. Thickness selection: less than 0.03mm results in insufficient mechanical strength, making it prone to breakage during tube insertion and bonding; greater than 0.15mm increases weight and material cost significantly. In-plane thermal conductivity is 1000-1800W / m·K; in this embodiment, 1500W / m·K is used. It can be placed over the entire surface area of the top and bottom of the honeycomb cell 31, or only in a localized high thermal conductivity area below the heat source; in this embodiment, it covers the entire compartment area. Advantages of full-surface laying: optimal global heat diffusion effect; local laying reduces costs. As an alternative, other high in-plane thermal conductivity materials such as graphene film, highly oriented pyrolytic graphite blocks, and compressed expanded graphite sheets can also be used.
[0069] The second adhesive layer 73 fills the gap (approximately 0.1-0.2 mm) between the pyrolytic graphite foil 72 and the microchannel conduit 4. It uses a high thermal conductivity silicone grease (such as Shin-Etsu G-751) with a thermal conductivity of 2-5 W / m·K; in this embodiment, 3.5 W / m·K is used. The silicone grease is chosen because it is soft, can fully fill the tiny gaps, and has low contact thermal resistance; its disadvantage is that it requires sealing to prevent drying. Alternatively, silicone adhesives, thermally conductive gels, or thermally conductive phase change materials (the latter having better long-term stability) can be used, either doped with ceramic fillers such as alumina, boron nitride, zinc oxide, or aluminum nitride.
[0070] V. Phase Change Material Thermal Storage Layer 8 In the area within the honeycomb cavity 31 where the microchannels 4 are not arranged, a phase change material heat storage layer 8 is filled. This embodiment uses a paraffin / expanded graphite composite phase change material (80% paraffin by mass, 20% expanded graphite). The reason for choosing paraffin / expanded graphite composite is that paraffin has a high latent heat (approximately 200 kJ / kg), and expanded graphite, as a framework, can prevent leakage and improve thermal conductivity. Alternatively, erythritol / graphene composite phase change materials, fatty acid-based phase change materials, hydrated salt-based phase change materials, or metal-based phase change materials can also be used. The phase change temperature can be selected within the range of 40-70℃; in this embodiment, 58℃ is chosen. The basis for selecting the phase change temperature is that the allowable operating temperature for spacecraft electronic products is typically -20℃ to +85℃. It is preferable to set the phase change point between 50-60℃ so that the heat storage layer activates before the chip reaches a dangerous temperature. The latent heat can be selected within the range of 150-250 kJ / kg; in this embodiment, 200 kJ / kg is chosen. If the latent heat is below 150 kJ / kg, the heat storage capacity will be insufficient; if it is above 250 kJ / kg, the phase change material will be expensive and may be unstable. The filling height is 80% of the height of the honeycomb core layer (approximately 11 mm), leaving space at the top to prevent thermal expansion from overflowing.
[0071] VI. Working Principle like Figure 5 As shown, the onboard high-performance computing unit (electronic device) is mounted on the outside of the upper panel 1 using standard fasteners. The heat generated during operation is transferred through the following path: First, the heat is rapidly diffused through the in-plane high thermal conductivity area of the upper panel 1; then, it is transferred to the pyrolytic graphite foil 72 via the first adhesive layer 71, and the pyrolytic graphite foil 72 further diffuses the heat along the in-plane direction to the area above the microchannel pipeline 4; next, the heat is transferred to the outer wall of the microchannel pipeline 4 via the second adhesive layer 73; coolant enters from one side manifold 5, is distributed to each microchannel pipeline 4, and flows at a flow rate of 0.3 m / s (adjustable within the range of 0.1-0.5 m / s), through convective heat transfer (convective heat transfer coefficient approximately...). The heat is carried away from the pipe wall and flows out from the other side of the manifold 5, entering the external pump-driven cooling circuit to complete the circulation. During transient peak loads, the phase change material heat storage layer 8 absorbs excess heat, maintaining the panel temperature near the phase change temperature and smoothing heat flow fluctuations. Coolant options include deionized water + 25% ethylene glycol (suitable for low-temperature environments), perfluorotriethylamine, FC-72, Galden, and other dielectric coolants (suitable for direct chip contact scenarios), or deionized water, ethylene glycol aqueous solution, propylene glycol aqueous solution, etc. Coolant selection criteria: dielectric coolants are safe but expensive; water-based coolants have high heat exchange efficiency but conductivity and freezing point must be considered.
[0072] VII. Performance Verification Based on theoretical calculations and finite element simulations, the performance of the cabin plate in this embodiment is as follows: areal density: (Top panel 10.8 + Bottom panel 20.8 + Honeycomb core layer 30.7 + Liquid cooling system 1.2 + Thermally enhanced interface 7 and phase change material thermal storage layer) ), satisfying less than Requirements.
[0073] In-plane thermal conductivity: 55 W / m·K (equivalent value), greater than 50 W / (m·K).
[0074] Equivalent thermal conductivity in the thickness direction: approximately 250 W / m·K, greater than 200 W / (m·K).
[0075] Heat dissipation capacity: Under conditions of coolant flow rate of 0.3L / min, inlet temperature of 20℃, and allowable temperature rise of 10℃, the total heat dissipation is 3.2kW, and the local heat flux density can reach [missing value]. greater than .
[0076] Structural performance: Bending stiffness of approximately 1200 N·m, first-order natural frequency > 200 Hz, meeting the load-bearing requirements of a typical satellite launch segment.
[0077] Example 2 (“Z” shaped arrangement – suitable for gradient heat load scenarios) The difference between this embodiment and embodiment 1 lies in the arrangement of the microchannel pipe 4 and the structure of the manifold 5. It is suitable for scenarios where the heat load is distributed in a gradient (such as a dense heat source and high heat flux density on one side of the cabin, and a sparse heat source and low heat flux density on the other side).
[0078] This embodiment employs a "Z"-shaped microchannel piping system 4. The "Z"-shaped arrangement refers to a stepped, gradually changing distribution of the piping from the inlet side to the outlet side of the cabin, with the flow channel length gradually varying from inlet to outlet. Specifically, the inlet side flow channel is short (low flow resistance, high flow rate), while the outlet side flow channel is long (high flow resistance, low flow rate). Combined with the variable diameter manifold 5 (larger inlet diameter, smaller outlet diameter), the coolant flow rate can be distributed as needed: a shorter flow channel is arranged in the area of high heat flux density (inlet side) to obtain a larger flow rate and enhance heat transfer; a longer flow channel is arranged in the area of low heat flux density (outlet side) to obtain a smaller flow rate to avoid overcooling and save pump power.
[0079] In this embodiment, the microchannel tubing is divided into 3 groups: Group 1 (high heat flux zone, 8 pieces): Flow channel length 8m, design flow rate 0.15L / min / piece; Group 2 (medium heat flow zone, 7 pieces): channel length 12m, design flow rate 0.10L / min / piece; Group 3 (low heat flux zone, 5 pieces): channel length 16m, design flow rate 0.075L / min / piece.
[0080] The manifold 5 adopts a variable diameter design, with an inlet diameter of 8mm, which gradually narrows to 5mm along the flow direction. The above flow distribution is achieved through flow resistance matching.
[0081] In scenarios with uneven heat source distribution, traditional uniformly arranged liquid cooling systems are prone to overheating in areas with concentrated heat sources and undercooling in areas with sparse heat sources. This embodiment utilizes a "Z"-shaped gradient arrangement with variable-diameter manifolds to achieve on-demand flow distribution—high flow rate in high heat flux zones (strong heat exchange capacity) and low flow rate in low heat flux zones (avoiding waste), resulting in a more uniform temperature distribution across the entire plate. Tests (finite element simulation) show that in scenarios with uneven heat source distribution… Under these conditions, the maximum temperature difference of the panel is less than 8°C, which is better than the "S"-shaped uniform arrangement in Example 1 (temperature difference less than 12°C), and the temperature uniformity is improved by about 33%.
[0082] Alternative variations: It is understood that the arrangement of the microchannel pipeline 4 can also adopt other forms such as "concentric circle" (suitable for circular heat sources), "radial" (suitable for heat sources at the center point to diffuse outwards), and "grid" (suitable for multi-point heat sources) according to the heat load distribution. These variations are all within the protection scope of this invention.
[0083] Example 3 (Dual-layer arrangement – suitable for extremely high power density scenarios) This embodiment provides another variant structure suitable for extremely high power densities. The difference from Embodiment 1 is that the microchannel tubing 4 adopts a double-layer arrangement. Specifically, a horizontal partition (using 0.1-0.3mm thick carbon fiber prepreg, fiberglass cloth, or other thin composite materials) is added in the middle of the honeycomb core layer 3 along its thickness direction, dividing the core layer into upper and lower sub-cavities (each sub-cavity is approximately 7mm high). Microchannel tubing 4 is arranged in each sub-cavity. The two layers of tubing 4 are connected at the edge of the compartment via a vertical connecting pipe (outer diameter 0.5-1.0mm, wall thickness 0.05-0.1mm), forming a three-dimensional flow channel.
[0084] Specific parameters: Upper microchannel tubing: 0.6mm outer diameter, 0.06mm wall thickness, 15 in total, arranged in the upper half of the honeycomb core layer.
[0085] Lower layer microchannels: 0.6mm outer diameter, 0.06mm wall thickness, 15 in total, arranged in the lower half of the honeycomb core layer.
[0086] Vertical connecting pipes: Located at the edge of the compartment, they can connect the upper and lower pipes in series (increasing the flow path length and improving the heat exchange time) or in parallel (increasing the total flow rate and reducing the pressure drop).
[0087] For certain special applications (such as laser weapon platforms, high-power phased array radar arrays, and space data center server bays), the heat flux density is extremely high. Furthermore, the heat dissipation area is limited, and a single-layer piping system may not provide sufficient heat exchange area. The double-layer design in this embodiment increases the heat exchange area by approximately 80% (from 20 pipes in a single layer to 30 pipes in a double layer). Under the same pressure drop conditions (less than 1 MPa), the heat dissipation capacity is increased to approximately 5 kW / plate (1m × 0.5m), and the areal density is approximately... (Still less than) (Within the constraints). Finite element simulation verification shows that the impact of the double-layer arrangement on the structural stiffness is less than 5% (because the partition is extremely thin and the overall height of the honeycomb core remains unchanged), and the bending stiffness is still greater than 1000 N·m, which meets the load-bearing requirements.
[0088] Alternative Variations: It should be noted that the dual-layer arrangement is not limited to two layers—where the core layer height allows (e.g., the compartment thickness is greater than 20mm), three or even more layers can be used to form a three-dimensional flow channel network. Furthermore, the upper and lower layer pipes can use different diameters, wall thicknesses, and materials to adapt to the heat dissipation requirements of different areas (for example, the upper layer corresponds to high heat flux chips, using small-diameter, densely arranged pipes; the lower layer corresponds to low heat flux devices, using large-diameter, sparsely arranged pipes).
[0089] Example 4 (Flat tube replacement – increasing thermally conductive contact area) The difference between this embodiment and Embodiment 1 lies in the cross-sectional shape and arrangement density of the microchannel pipeline 4. In this embodiment, the microchannel pipeline 4 uses a flat rectangular cross-section metal tube (cross-sectional size 0.3mm × 1.0mm, wall thickness 0.05mm) instead of the circular cross-section tube in Embodiment 1.
[0090] The circular tube has a line contact with the pyrolytic graphite foil 72, requiring a second adhesive layer 73 (high thermal conductivity silicone grease) for filling. However, even after filling, the adhesive layer itself still has a certain thermal resistance. The flat tube, with its top and bottom surfaces being planar, has a surface contact (rather than a line contact) with the pyrolytic graphite foil 72 and the honeycomb cavity 31 wall, effectively increasing the thermally conductive contact area (by approximately 60%) and reducing contact thermal resistance. Simultaneously, due to the tighter contact, the dependence on the second adhesive layer is reduced. Even if the adhesive layer ages or dries out during long-term use, it can still maintain a certain level of thermal conductivity, improving long-term reliability.
[0091] The flat tubes are arranged with a higher density within the honeycomb core layer 3: the center-to-center distance between adjacent tubes is 10 mm (20 mm in Example 1), with a total of 40 tubes arranged to cover the entire compartment area. Since the flat tubes are only 0.3 mm thick, they occupy a smaller proportion of the honeycomb core layer height (14 mm), leaving more space for the phase change material heat storage layer 8.
[0092] Test comparison (finite element simulation): Under the same coolant flow rate (0.3L / min) and inlet temperature (20℃), the maximum temperature difference of the panel in this embodiment is 4℃, which is further reduced compared to 5℃ in Example 1; the total heat dissipation is 3.5kW, which is about 9% higher than 3.2kW in Example 1.
[0093] Alternative variations: It is understood that the cross-section of the microchannel pipe 4 can also be elliptical, D-shaped, trapezoidal, or other irregularly shaped, as long as it can increase the contact area with the heat diffusion layer. Materials can also be Inconel 718 high-temperature alloy (suitable for near-solar orbit environments above 450°C), titanium alloy Ti-6Al-4V (higher strength, suitable for deep-sea / deep-space high-pressure environments), copper alloy (better thermal conductivity but higher density, suitable for ground or manned spaceflight scenarios where weight is not critical), etc.
[0094] Example 5 (Comparative Experiment - Adhesive Performance with Different GnP Contents) To verify the effect of GnP content in the first adhesive layer 71 of the thermally enhanced interface 7 on heat transfer performance, this embodiment provides comparative experimental data for different GnP contents. Five groups of samples (100mm × 100mm × 0.2mm) were prepared, using modified epoxy resin adhesives with GnP contents of 0wt% (pure epoxy resin), 1wt%, 2wt%, 3wt%, and 5wt%, respectively, and their thermal conductivity and adhesive shear strength were tested.
[0095]
[0096] Experimental results show that when the GnP content is 1-3 wt%, the thermal conductivity of the adhesive increases from 0.2 W / m·K to 1.2-3.2 W / m·K, while maintaining high adhesive strength (shear strength greater than 15 MPa), meeting the adhesive bonding requirements for spacecraft structures (typically requiring a shear strength greater than 10 MPa). When the GnP content exceeds 5 wt%, although the thermal conductivity further increases to 4.0 W / m·K, the adhesive strength significantly decreases to below 10 MPa, posing a risk of structural failure. Therefore, the preferred GnP content in the first adhesive layer 71 is 1-3 wt%, with 2 wt% being optimal.
[0097] It should be noted that the above data uses graphene nanosheets as filler. If other fillers (such as carbon nanotubes, diamond powder, boron nitride, etc.) are used, the optimal content range may need to be adjusted accordingly, but the overall trend remains the same: there is a balance point between thermal conductivity and strength. Excessive filler content will lead to a decrease in mechanical properties due to increased defects at the filler-resin interface. In practical engineering applications, the optimal content can be selected within the range of 1-5 wt%, depending on specific mechanical requirements (the severity of the mechanical environment of the transmitter segment) and heat dissipation requirements (the heat flux density of the chip).
[0098] Example 6 - Manufacturing Method Example Reference Figure 5 This embodiment provides a manufacturing method, including the following steps: S1: Prepare the upper panel 1 and the lower panel 2 High thermal conductivity carbon fiber prepreg is laid up according to the designed layup angle and sequence. After layup, it is placed in a hot press mold and cured for 30-120 minutes (typical values: 120℃, 135℃, 150℃, 165℃, 180℃) at a temperature of 120-180℃ (typical values: 120℃, 135℃, 150℃, 165℃, 180℃) and a pressure of 0.5-1.5MPa (typical values: 0.5MPa, 0.8MPa, 1.0MPa, 1.2MPa, 1.5MPa) (typical values: 30min, 45min, 60min, 90min, 120min) under conditions of 120-180℃ and 0.5-1.5MPa (typical values: 0.5MPa, 0.8MPa, 1.0MPa, 1.2MPa, 1.5MPa) and 0.3-0.8mm after curing. The outer surface of the panels is coated with a functional coating (one or more of electromagnetic shielding coating, anti-ionic oxygen coating, and high emissivity thermal control coating) according to the requirements of the track environment.
[0099] S2: Prepare the honeycomb core layer 3 and insert microchannels 4 The carbon fiber paper honeycomb core is cut to the size of the compartment panel, and guide holes 32 are machined at the predetermined insertion positions of the microchannels 4 (using methods such as CNC drilling, laser drilling, or punching). Metal tubes (titanium alloy, stainless steel, Inconel alloy, etc.) are straightened and surface roughened (using methods such as micro-arc oxidation, anodizing, chemical etching, sandblasting, and laser texturing) and then inserted into the honeycomb cells 31 along the guide holes 32 to form the microchannels 4. The ends of the microchannels 4 converge at the edge of the compartment panel and are connected to the manifold 5 by argon arc welding, laser welding, brazing, or mechanical connection. After welding, an airtightness test is performed. .
[0100] S3: Set thermally enhanced interface 7 An epoxy resin adhesive containing GnP (or other high thermal conductivity fillers) is uniformly coated on the bonding surfaces of the top panel 1, the bottom panel 2, and the honeycomb core layer 3 to form a first adhesive layer 71; pyrolytic graphite foil 72 (or graphene film, highly oriented pyrolytic graphite blocks, etc.) is laid on the top and bottom of the honeycomb cell 31; and high thermal conductivity silicone grease (or thermally conductive gel, thermally conductive phase change material, organic silicone adhesive with ceramic fillers, etc.) is filled in the gap between the pyrolytic graphite foil 72 and the microchannel pipeline 4 to form a second adhesive layer 73.
[0101] S4: Adhesive bonding and curing form an integrated structure. The upper panel 1, lower panel 2, honeycomb core layer 3, microchannel pipeline 4, and thermally enhanced interface 7 are assembled sequentially in an assembly fixture. A uniform pressure of 0.1-0.3 MPa (typical values: 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa) is applied, and the mixture is cured for 2-6 hours (typical values: 2 hours, 3 hours, 4 hours, 5 hours, 6 hours) at a temperature of 80-120℃ (typical values: 80℃, 90℃, 100℃, 110℃, 120℃) to form an integrated load-bearing and heat dissipation compartment. After curing, overall airtightness testing, flatness testing (flatness less than 0.5 mm / m), and structural performance testing are performed.
[0102] This manufacturing method employs a "tube-insertion followed by bonding" process sequence—that is, microchannel tubes are first inserted into the honeycomb cell cavity, and then the panel and honeycomb core are bonded and cured. The advantage of this sequence is that if the panel is bonded first and then the tubes are inserted, the tubes cannot enter the closed honeycomb cell cavity; if pre-embedded tubes are used before foaming, the accuracy of the tube position is difficult to guarantee. This method uses guide holes to precisely position the tube path, ensuring accurate alignment of the tubes with the predetermined heat source area. Simultaneously, uniform pressure is applied during bonding and curing, causing the thermally enhanced interface layers to adhere tightly, forming a low thermal resistance thermal conductivity pathway.
[0103] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art can make various improvements and modifications without departing from the spirit and principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A carbon fiber honeycomb sandwich panel based on microchannel liquid cooling, characterized in that, include: The upper panel (1) and the lower panel (2) are made of high thermal conductivity carbon fiber prepreg by hot pressing and curing, and are set as the skin of the honeycomb sandwich structure to bear the in-plane load and in-plane heat conduction; The honeycomb core layer (3) is fixed between the upper panel (1) and the lower panel (2), and adopts a carbon fiber paper honeycomb core or an aramid paper honeycomb core. The honeycomb cavities (31) of the honeycomb core layer (3) serve as components of the coolant flow channel. The honeycomb core layer (3) is composed of a regular hexagonal honeycomb structure made of carbon fiber paper. The microchannel liquid cooling system is embedded in the honeycomb grid cavity (31) inside the honeycomb core layer (3), including microchannel pipes (4) passing through the honeycomb grid cavity (31). The thermally enhanced interface (7) is used to reduce the out-of-plane thermal resistance between the upper panel (1), the lower panel (2) and the honeycomb core layer (3), to diffuse the heat of the panel along the in-plane direction to the area covered by the microchannel pipeline (4), and to eliminate the gap thermal resistance between the microchannel pipeline (4) and the surrounding structure. The thermally enhanced interface (7) includes: a first adhesive layer (71) coated between the upper panel (1), the lower panel (2) and the honeycomb core layer (3), a pyrolytic graphite foil (72) embedded in the top and bottom of the honeycomb cell (31), and a second adhesive layer (73) filled between the pyrolytic graphite foil (72) and the microchannel pipeline (4).
2. The cabin panel according to claim 1, characterized in that, The first adhesive layer (71) is a modified epoxy resin adhesive doped with 1-5 wt% graphene nanosheets, with a thickness of 0.1-0.3 mm and a thermal conductivity of 1.5-3.0 W / m·K; the second adhesive layer (73) is a high thermal conductivity silicone grease or an organic silicone adhesive doped with ceramic fillers, with a thermal conductivity of 2-5 W / m·K.
3. The cabin panel according to claim 1, characterized in that, The pyrolytic graphite foil (72) has a thickness of 0.03-0.15 mm and an in-plane thermal conductivity of 1000-1800 W / m·K. It is placed on the entire surface area or local high thermal conductivity areas at the top and bottom of the honeycomb cell cavity (31).
4. The cabin panel according to claim 1, characterized in that, The microchannel liquid cooling system also includes a manifold (5) located at the edge of the cabin and connected to the end of the microchannel pipeline (4), and an interface (6) located on the side of the cabin and connected to the manifold (5).
5. The cabin panel according to claim 1, characterized in that, The upper panel (1) and lower panel (2) are made of high modulus pitch-based carbon fiber prepreg with a fiber volume fraction of 50-60%, a panel thickness of 0.3-0.8 mm, an in-plane thermal conductivity greater than 300 W / m·K, and a layup pattern of [0° / 90° / 0° / 90°] symmetrical layup or quasi-isotropic layup.
6. The cabin panel according to claim 1, characterized in that, The microchannels (4) are arranged in an “S” shape in a continuous manner, a “Z” shape in a gradual manner, a concentric circle arrangement, or a radial arrangement within the honeycomb core layer (3).
7. The cabin panel according to claim 1, characterized in that, The honeycomb core layer (3) has a guide hole (32) pre-processed in the area through which the microchannel pipeline (4) passes. The diameter of the guide hole (32) is 0.1-0.3 mm larger than the outer diameter of the microchannel pipeline (4).
8. The cabin panel according to claim 1, characterized in that, It also includes a phase change material heat storage layer (8), which fills the area inside the honeycomb grid cavity (31) where no microchannel pipeline (4) is arranged. The phase change material heat storage layer (8) is made of composite phase change material with a phase change temperature of 40-70℃ and a latent heat of 150-250kJ / kg.
9. The cabin panel according to claim 1, characterized in that, The microchannel liquid cooling system adopts a double-layer arrangement. A horizontal partition is set in the middle of the thickness direction of the honeycomb core layer (3) to divide the core layer into two sub-cavities. Microchannel pipelines (4) are arranged in each sub-cavity. The two layers of pipelines are connected by a vertical connecting pipe.
10. The cabin panel according to claim 1, characterized in that, The outer surfaces of the upper panel (1) and the lower panel (2) are provided with functional coatings, including at least one of an electromagnetic shielding coating, an antigen oxygen coating, and a high emissivity thermal control coating.
11. A spacecraft cabin structure, characterized in that, Including the carbon fiber honeycomb sandwich panel based on microchannel liquid cooling as described in any one of claims 1-10.
12. A method for manufacturing a carbon fiber honeycomb sandwich panel based on microchannel liquid cooling, characterized in that, Includes the following steps: S1: High thermal conductivity carbon fiber prepreg is used to lay up the layers according to the designed layup angle and sequence, and then hot-pressed and cured for 30-120 minutes at a temperature of 120-180℃ and a pressure of 0.5-1.5MPa to prepare the upper panel (1) and the lower panel (2). S2: Cut the carbon fiber paper honeycomb core or aramid paper honeycomb core according to the size of the cabin plate, process guide holes (32) at the predetermined insertion positions, and insert titanium alloy or stainless steel thin tubes with surface micro-arc oxidation treatment into the honeycomb cell cavity (31) through the guide holes (32) to form microchannel pipelines (4). The end of the microchannel pipeline (4) is connected to the manifold (5), and the air tightness is tested after connection. S3: Set up a thermally enhanced interface (7): Apply an epoxy resin adhesive containing graphene nanosheets to the bonding surface of the top plate (1), the bottom plate (2) and the honeycomb core layer (3) to form a first adhesive layer (71), lay pyrolytic graphite foil (72) on the top and bottom of the honeycomb cavity (31), and form a second adhesive layer (73) between the pyrolytic graphite foil (72) and the microchannel pipeline (4) with high thermal conductivity silicone grease or silicone adhesive. S4: Assemble the upper panel (1), lower panel (2), honeycomb core layer (3), microchannel pipeline (4) and thermally enhanced interface (7) in sequence in the assembly fixture, apply a uniform pressure of 0.1-0.3MPa, and cure at a temperature of 80-120℃ for 2-6 hours to form a load-bearing and heat dissipation integrated carbon fiber honeycomb sandwich panel.
Citation Information
Patent Citations
Wing antenna integrating structures and functions
CN103887605A
A lightweight spacecraft main structure
CN107745829B
Microchannel cooling of high power semiconductor devices
US5801442A
Electroosmotic microchannel cooling system
US6942018B2
Spacecraft And Spacecraft Radiator Panels With Composite Face-sheets
CN105775172A
